PERANCANGAN MEDIA PEMBELAJARAN MATEMATIKA MENGGUNAKAN TEKNOLOGI AUGMENTED REALITY: Design of Mathematics Learning Media Using Augmented Reality Technology - Alfisyahra, Alfisyahra; Karniman, Tegoeh S.; Tawil, Akhyar H.M (Aksioma, 2024)
Mathematics and technology will continue to work together to form a system because in building the system requires the application of mathematics. The contribution of mathematics is included in a very large scale in the intervention of technological development in the world. Mathematics itself is related to computers or IT in terms of finding rational logical equations so that they can be translated into computers using programming languages ​​and the relationship in carrying out rational mathematical calculations quickly and accurately. Thus in learning mathematics, the role of technology is needed, some of which function as tools for doing mathematical calculations, creating interesting mathematical learning designs for students, and as a medium for teaching and learning mathematics. One of the uses of technology in learning mathematics is the creation of learning media based on augmented reality technology. In learning, Augmented Reality technology functions as a learning medium that can display virtual objects into the real world. Learning media is very much needed by teachers to help deliver material in a learning process. The purpose of this study is to produce mathematics learning media using android-based augmented reality technology so that students can visualize mathematics learning easily using interactive media. Learning media is developed referring to the ADDIE development model, namely Analysis, Design, Development, Implementation, and Evaluation. The data needed in this study will be collected through classroom observations, questionnaires, interviews, and literature studies. The media that has been developed will be tested to assess its feasibility and the media is said to be valid if the test results are in the good/feasible category.